Scale of attitude towards research, students and professional engineering and science careers of the National University of Engineering - Huamanchumo de la Cuba, Luis E. (2006)
Understanding the structure of the formation of attitudes towards research will allow the design of teaching and application strategies aimed at reversing the tendency to minimize the relevance of research. The empirical evidence confirms that the formation of the scale of attitudes towards research in the students of the professional engineering and science careers of the National University of Engineering has a multidimensional character, which is structured by the following factors that explain 42.9% of total inertia, namely: (1) Importance of research for society and personal life, (2) Institutional environment and (3) Modeling and analysis of statistical data. We worked with a sample of 382 students for which it was necessary to develop suitable data collection instruments for latent structures.